Design and Implementation of Flexible Four-Bar-Mechanism-Based Long-Stroke Micro-Gripper - Liangyu Cui; Haonan Zhu; Xiaofan Deng; Yuanyuan Chai (Actuators, 2025)
To meet the demand for submillimeter-level gripping capabilities in micro-grippers, an amplification mechanism based on a flexible four-bar linkage is proposed. The micro-gripper designed using this mechanism features a large gripping stroke in the millimeter range. First, the amplification effect of the flexible four-bar linkage was structurally designed and theoretically analyzed. Through kinematic analysis, a theoretical model was developed, demonstrating that the flexible four-bar linkage can achieve an extremely high amplification factor, thus providing a theoretical foundation for the design of the micro-gripper. Then, kinematic and mechanical simulations of the micro-gripper were conducted and validated using ANSYS 2025 simulation software, confirming the correctness of the theoretical analysis. Finally, an experimental platform was set up to analyze the characteristics of the micro-gripper, including its stroke, resolution, and gripping force. The results show that the displacement amplification factor of the gripper designed based on the flexible four-bar linkage can reach 40, with a displacement resolution of 50 nm and a gripping range of 0–880 μm. By using capacitive displacement sensors and strain sensors, integrated force and displacement control can be realized. The large-stroke micro-gripper based on the flexible four-bar linkage is compact, with a large stroke, and has broad application prospects.